Advances in chemical physics. analytic and computational methods - Miller, J.J.H. (John James Henry) 1937- (John Wiley & Sons, 1997)
An important addition to the Advances in Chemical Physics series, this volume makes available for the first time in English the work of leading Russian researchers in singular perturbation theory and its application. Since boundary layers were first introduced by Prandtl early in this century, rapid advances have been made in the analytic and numerical investigation of these phenomena, and nowhere have these advances been more notable than in the Russian school of singular perturbation theory.